Information handling in collaborative research - Collins, Ellen; Jubb, Michael (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2013)
UK public policy makers have a growing interest in collaborative research, where academics work with public, private or third sector partners on a joint project which supports the partner’s aims. This paper reports on the findings of five case studies, looking at how information is sourced, managed, used and shared within collaborative research projects. It finds that researchers within collaborative projects have similar information management issues as are known to exist within academia more broadly, but that the specific conditions which govern research collaborations mean that interventions to improve or support information management must be carefully tailored.